Pour un développement sain : (Banque Mondiale, 2009)
Healthy Development: The World Bank Strategy for Health, Nutrition, & Population Results" updates the Bank's contribution to improving health outcomes. Including the 2015 Millennium Development Goals, at a time when new and existing multilateral organizations, bilateral partners, and foundations are increasing their commitment to global health. After an extensive consultative process with governments and global partners, including civil society organizations and bilateral and multilateral organizations, the World Bank's new health, nutrition, and population